Children's growth and poverty in rural Guatemala - Gragnolati, Michele (Policy research working paper, 1999)
Research conforms that poor child growth outcomes in Guatemala are the result of widespread poverty. The better the parents' education and household income, the less likely children are to suffer from malnutrition. Children also fare better where community infrastructure (such as piped water and garbage disposal) and health care facilities are better